DOPPLEROGRAPHIC PREDICTORS OF COGNITIVE STATUS DYNAMICS OF PATIENTS AFTER CAROTID ANGIOPLASTY WITH STENTING - A. A. Narzullaev; A. V. Savello; D. V. Svistov; S. A. Landik; K. V. Simakov; A. S. Gus’Kov (Вестник хирургии имени И.И. Грекова, 2018)
The authors present dopplerographic predictors of cognitive status dynamics of patients undergoing carotid angioplasty with stenting. It was stated that the cognitive status dynamics depended on the initial condition of patients and reactivity coefficient on hypercapnia in target vascular pool.